Reinforcing hegemonic structures: remediating and stymieing memories of Native Americans at Euro-American historic sites in the American West - Stocker, Esther, author; Dunn, Thomas, advisor; Dickinson, Greg, committee member; Martinez, Doreen, committee member (Colorado State University. Libraries, 2024)
This thesis examines the Crazy Horse Memorial and the Little Bighorn Battlefield National Monument to better understand how both places of public memory articulate Native American identities. Drawing on scholarship in public memory, the materiality of rhetoric, and Native American rhetorics, this analysis shows in part how both sites strive to remediate public memories related to Native Americans in the broader U.S. culture. However, the chapters also show that these efforts at Crazy Horse and Little Bighorn are simultaneously stymied from within and without through intentional and unintentional means. As the chapters reveal, the stymying components of each memorial presents a specific articulation of Native identity with the Crazy Horse Memorial presenting Native identities as ownable and the Little Bighorn Battlefield National Monument presenting Native identities as existing in the past, respectively. Putting both presentations into conversations suggests that there is a broader cultural articulation of Native identity as controllable in these U.S.-American memory sites. Such a rhetoric perpetuates prioritizing Euro-American values, stories, and identities within the U.S.
Keywords: materiality; public memory; colonization; rhetoric; Native American history